Innovation Mirage: The Role of Technological Uncertainty in Military Instability - I. A. Istomin (Vestnik MGIMO-Universiteta)
The article examines the impact of technological changes on the risks of military clashes between states. Currently, experts express increasing concerns about the destabilizing effect of new weapons (including anti-missile and anti-satellite weapons, hypersonic missiles, autonomous lethal systems, and artificial intelligence). These assessments are rarely based on solid theoretical foundations. The author seeks to fill this gap, arguing that the emergence of new weapons has a negative impact on international stability, and this effect is weakly related to the specific characteristics of underline technologies. The theory of technological uncertainty offers an alternative to the offense-defense balance theory. The latter developed since the 1970s, but its validity is questionable. The theory of technological uncertainty attributes the destabilizing effect of weapons to the divergence of states' perceptions of the balance of powers, to the hyped expectations regarding the ability to compensate quantitative limitations with qualitative superiority, to the alarmistic sense of closing windows of opportunities and growing vulnerabilities. The article tests the theory against the historical record of military clashes in Europe from the end of the 18th to the middle of the 20th centuries, as well as the crises between superpowers during the Cold War. The empirical cases are selected in order to cover the period marked by the intensification of qualitative arms races between states. In addition, it is also the period most often used to substantiate the offense-defense balance theory. The history of the last two and a half centuries provides a solid foundation for the theory of technological uncertainty. All instances of large-scale military clashes were preceded by significant technological changes, while peace fell on periods of technological stagnation. The author addresses the policy implications of the theory for the discussions on emerging weapons in the 2010s and 2020s. The study confirms that concerns regarding their destabilizing effect are justified, but for the different reasons from those put forward by most analysts. A somewhat optimistic caveat to its conclusions is the fact that currently emerging weapons are at various stages of development. The greatest likelihood of military clashes corresponds to the overlap of several technological uncertainties. Therefore, an increase in the time lag between introduction of various arms can mitigate destabilizing effect.